Electronic government : 19th IFIP WG 8. 5 International Conference, EGOV 2020, Linköping, Sweden, August 31-September 2, 2020, Proceedings /: 19th IFIP WG 8. 5 International Conference, EGOV 2020, Linköping, Sweden, August 31-September 2, 2020, Proceedings. (2020) - Unknown
No abstract available